The impact of the COVID-19 pandemic on glycaemic control in people with diabetes: A systematic review and meta-analysis - O’Mahoney, LL; Highton, PJ; Kudlek, L; Morgan, J; Lynch, R; Schofield, E; Sreejith, N; Kapur, A; Otunla, A; Kerneis, S; James, O; Rees, K; et al. (Wiley, 2022)
Covid-19 pandemic and lock down (LD) has affected diabetes care. We aimed to identify, appraise and synthesise available evidence on the impact of the pandemic on glycaemic control in people with diabetes.